Enhancing bioelectricity generation of bio-electrochemical reactors using porous nickel-based composite as effective oxygen reduction catalyst. (20th December 2020) - Li, Meng; Li, Yan-Wen; Yu, Xiao-Long; Xiang, Lei; Zhao, Hai-Ming; Yan, Jian-Fang; Feng, Nai-Xian; Xu, Ming-Yi; Cai, Quan-Ying; Mo, Ce-Hui
Abstract: Microbial fuel cell as a sustainable microbial-electrochemical reactor can harvest bio-power from wastewater by the oxidation of electro-active bacteria on the anode, while its power output is greatly relying on the oxygen reduction reaction performance of the cathode electro-catalysts. Here, the dahlia flower-like nickel-based composites have been synthesized through a hydrothermal reaction, and was used as an efficient oxygen reduction reaction catalyst in a single chamber microbial fuel cell. The physical characterization of surface structure suggests the composites have successfully prepared. The MFC with Ni-melamine cathode can achieve obviously higher power density of 378.08 mW m −2 than those of Ni-urea cathode (244.02 mW m −2 ) and Ni-dicyandiamide cathode (201.67 mW m −2 ). A series of electrochemical characterization suggests that Ni-melamine electrode possesses larger electrochemical active surface area, lower charge transfer resistance, and higher oxygen reduction performance than those of Ni-urea electrode and Ni-dicyandiamide electrode. The electrochemical measurements have also demonstrated that nickel-melamine composites can be involved in oxygen reduction reaction via a four-electron route due to the high-efficient electrocatalytic activity. In addition, the maximum power density of nickel-based composites is obviously increased with an increase of catalysts coating amounts. When the loading amounts are 4 mg cm −2, the power density for nickel-based composites is improved to 1421.4 mW m −2, which is 1.68 times higher than that of Pt/C due to the introduction of oxygen vacancies and nitrogen element. Thus, nickel-based composite is an effective and promising catalyst material for microbial fuel cell to substitute Pt/C for oxygen reduction reaction application. Graphical abstract: Image 1 Highlights: Porous Nickel-based composites were used as catalyst for MFCs. The ORR of Ni-M occurred via a four-electron transfer route. The Ni-M was a promising electro-catalyst for single chamber MFC. The Ni-M had a stable power output in long term operation.